2002
DOI: 10.1152/ajpheart.00535.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hypovolemia and neurovascular control during orthostatic stress

Abstract: Humans exposed to real or simulated microgravity experience decrements in blood pressure regulation during orthostatic stress that may be related to autonomic dysregulation and/or hypovolemia. We examined the hypothesis that hypovolemia, without the deconditioning effects of bed rest or spaceflight, would augment the sympathoneural and vasomotor response to graded orthostatic stress. Radial artery blood pressure (tonometry), stroke volume (SV), brachial blood flow (Doppler ultrasound), heart rate (electrocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 44 publications
9
66
2
3
Order By: Relevance
“…Significant elevations were observed in plasma norepinephrine in the muscle chemoreflex, cold pressor, and lower body suction tests. These data are consistent with observations from direct measurement of muscle SNA (MSNA) during muscle ischemia (39), cold pressor test (33), and lower body suction (23,31). The effects of mental stress are equivocal, with some studies showing a small increase in MSNA (5), whereas with others there was a decrease (16).…”
Section: Sympathetic Activation and Stress Responsesupporting
confidence: 82%
See 1 more Smart Citation
“…Significant elevations were observed in plasma norepinephrine in the muscle chemoreflex, cold pressor, and lower body suction tests. These data are consistent with observations from direct measurement of muscle SNA (MSNA) during muscle ischemia (39), cold pressor test (33), and lower body suction (23,31). The effects of mental stress are equivocal, with some studies showing a small increase in MSNA (5), whereas with others there was a decrease (16).…”
Section: Sympathetic Activation and Stress Responsesupporting
confidence: 82%
“…In the study of Hijmering et al, subjects were supine for at least 90 min before the application of the final level of lower body suction, and this might have accounted for the Ͼ15% elevation in heart rate (18), whereas heart rate in the current study and other research (3,31) showed little or no increase until lower body suction exceeded Ϫ20 mmHg. Even though heart rate increased very little with Ϫ20 to Ϫ30 mmHg lower body negative pressure, MSNA is increased by lower body suction (23,31,38). It is possible that prolonged supine posture might have interacted with the lower body suction to modify the cardiovascular response, resulting in elevated heart rate, as has been observed after very short durations of slight head-down bed rest (2,25).…”
Section: Sympathetic Activation and Stress Responsementioning
confidence: 97%
“…This assumption is based on the important role of the sympathetic nervous system in volume homeostasis via renal innervation and the renin-angiotensin system (6). In addition, a relation is present between baroreflex-mediated vascular control (26), time to presyncope (10), and blood pressure during orthostatic challenges in autonomic failure (46). In addition, plasma volume expansion is considered an effective therapy in PD patients with OH (38).…”
mentioning
confidence: 99%
“…It has been demonstrated in numerous studies that, during tilting to erect position or HUT, noradrenaline, adrenaline and vasopressin concentrations increased significantly after several minutes of the test, reaching a constant value, which remained unchanged until test completion. [18][19][20] This was true, even if a significant BP decrease and/or HR reduction (fainting) developed in the subject.In addition, the Renin-AngiotensinAldosterone (R-A-A) system activation occurred only after about 15-20 min of HUT. [20] In our HUT study, syncope developed between minutes 15th and 17th.…”
Section: Discussionmentioning
confidence: 99%